The Influence of Attraction and Social Media-Based Promotion on Visitor Numbers at the Bajra Sandhi Monument of the Balinese People's Struggle - Ni Made Dwipayanti; I Made Arsa Wiguna; I Gede Sedana Suci (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the influence of attraction and social media-based promotion on visitor numbers to the Bajra Sandhi Monument, a significant historical and cultural landmark in Bali. In recent years, the monument has seen a decline in the number of visitors, prompting the need for this research to explore the factors contributing to the downturn. The study employs a quantitative approach with data collected through the distribution of questionnaires. A probability sampling technique was applied, selecting 100 respondents who were visitors to the monument. The research instrument consisted of a validated and reliable questionnaire to ensure accuracy and consistency. Data analysis was conducted using multiple linear regression to examine the impact of each independent variable—attraction (X1) and social media-based promotion (X2)—on the dependent variable, which is the number of visitors (Y). The regression equation derived from the analysis is Y = 17.266 + (0.237)X1 + (0.285)X2, with a t-table value of 1.662, an F-table value of 3.09, and a significance level of 5%. The partial tests revealed that both variables significantly influenced visitor numbers. The attraction (X1) had a t-value of 2.100, which was greater than the t-table value (1.662), and a significance level of 0.038, indicating a 12.7% contribution to visitor numbers. Similarly, social media-based promotion (X2) had a t-value of 2.607 and a significance level of 0.011, contributing 16.3%. The simultaneous test produced an F-value of 19.930, which exceeded the F-table value, with a significance of 0.000, indicating that both variables together significantly affected visitor numbers. The adjusted R² value of 0.277 suggests that 27.7% of the variation in visitor numbers is explained by attraction and social media promotion, while the remaining 72.3% is influenced by other factors not examined in this study.